Early Detection of Ovarian Cancer using the Risk of Ovarian Cancer Algorithm with Frequent CA125 Testing in Women at Increased Familial Risk - Combined Results from Two Screening Trials - Skates, Steven J; Greene, Mark H; Buys, Saundra S; Mai, Phuong L; Brown, Powel; Piedmonte, Marion; Rodriguez, Gustavo; Schorge, John O; Sherman, Mark; Daly, Mary B; Rutherford, Thomas; Brewster, Wendy R; et al. (Clinical cancer research, 2017)
Women at familial/genetic ovarian cancer risk often undergo screening despite unproven efficacy. Research suggests each woman has her own CA125 baseline; significant increases above this level may identify cancers earlier than standard 6- to 12-monthly CA125 > 35 U/mL. Data from prospective Cancer Genetics Network and Gynecologic Oncology Group trials, which screened 3,692 women (13,080 woman-screening years) with a strong breast/ovarian cancer family history or mutations, were combined to assess a novel screening strategy. Specifically, serum CA125 q3 months, evaluated using a risk of ovarian cancer algorithm (ROCA), detected significant increases above each subject's baseline, which triggered transvaginal ultrasound. Specificity and positive predictive value (PPV) were compared with levels derived from general population screening (specificity 90%, PPV 10%), and stage-at-detection was compared with historical high-risk controls. Specificity for ultrasound referral was 92% versus 90% ( = 0.0001), and PPV was 4.6% versus 10% ( > 0.10). Eighteen of 19 malignant ovarian neoplasms [prevalent = 4, incident = 6, risk-reducing salpingo-oophorectomy (RRSO) = 9] were detected via screening or RRSO. Among incident cases (which best reflect long-term screening performance), three of six invasive cancers were early-stage (I/II; 50% vs. 10% historical controls; = 0.016). Six of nine RRSO-related cases were stage I. ROCA flagged three of six (50%) incident cases before CA125 exceeded 35 U/mL. Eight of nine patients with stages 0/I/II ovarian cancer were alive at last follow-up (median 6 years). For screened women at familial/genetic ovarian cancer risk, ROCA q3 months had better early-stage sensitivity at high specificity, and low yet possibly acceptable PPV compared with CA125 > 35 U/mL q6/q12 months, warranting further larger cohort evaluation. .